PERLINDUNGAN HUKUM HAK ATAS TANAH PENDUDUK BERSERTIFIKAT DALAM REGISTER KEHUTANAN DI DESA TANGGA KECAMATAN AEK SONGSONGAN KABUPATEN ASAHAN - MERITAKEN SURBAKTI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Muhammad Yamin3. Syafruddin Kalo There is a conflict over the land and natural resources which possession and management are organized by the people who makes use of the forestry area. The possession and management of forestry area are granted by Forestry Department whereas land is provided by the National Land Agency. This has encouraged the National Land Agency in Asahan District to make regulations concerning the management of forestry area borders which is in line with the Land Act No. 5/1960. By these procedures, a certificate is issued for the land in the forestry registry area. The ownership certificate of the land in the forestry registry area is contrary to the regulations in Law No. 18/2013; which leads to obscure liabilities and to disputes over land authority and ownership.Based on the results of the research, it is found out that the legal consequence of the certified land in the forestry area at Tangga Village is that a lawsuit can be filed against the revocation of the land certificates to PTUN (Administrative Court). The legal protection for the certified land owners in the forestry area in Tangga Village is that the ownership is valid and admitted by the Land Act No. 5/1960 as stated in Article 19 and the land registration that has been complied with the procedures is pronounced to be valid as land certificates. The synchronization between the Land Act No. 5/1960 and Forestry Law No. 19/2004 should be made through a Memorandum of Understanding between the National Land Agency and the Forestry Ministry so that the certificate issuance will not be legally defective or revocable, and cause loss to the society.It is suggested that The Asahan District Government pay more attention to the land registration so that it will not violate people’s land title. It is also suggested that the National Land Agency and PPAT (Officials Empowered to Draw up land Deeds) be selective during the registration process in order to gain the legal certainty for the certificate, and a Memorandum of Understanding be made between national Land Agency and the Forestry Ministry in Asahan District so that the land registration and certificate issuance will result in synergy. It is recommended that the Forestry Agency in Asahan District make measurements and regulations concerning the borders of the forestry area indicating which land is included into the State Forestry area or people’s land, so that these regulations can be a reference to issue a certificate.Keywords: Legal Protection, Certified Land, Forestry Registry